IMPLEMENTASI KEBIJAKAN SISTEM RESI GUDANG SEBAGAI UPAYA PENINGKATAN POSISI TAWAR PETANI KECIL (STUDI DI KABUPATEN CIANJUR JAWA BARAT) - Jayani, Santi; Nugroho, Fentiny (Istek Widuri Jakarta, 2019)
This study examines implementation of the Warehouse Receipt System (SRG) as an effort to increase the bargaining position of small farmers in Cianjur Regency, West Java. The study adopts George Edwards III's policy implementation model, which says policy implementation is influenced by four factors, namely communication, resources, the propensity of implementing policies and organizational structure. Among many SRG warehouses in Indonesia, the warehouse in Cianjur Regency, in particular, is the best-performingone, therefore the research in this location is expected to give significant overview of its implementation. This study uses a qualitative approach with a descriptive research type. Data collection was conducted through in-depth interview to eight respondents and field observation. The study shows that stakeholders have implemented the provisions included in this model of four factors. However, there are some aspects that need more attention because SRG has a great potential given that agriculture is the main livehood in Cianjur Regency.SRG has indirect impact to farmers’ welfare, and its implementation reflects the social development approach, the one that connects and integrates economic and social policies. This policy implementation provides opportunities for farmers to get better offers for their agricultural production. By participating in the SRG system, farmers can postpone selling and have the opportunity to get better prices as well as to improve the quality of their commodities, which in turn has an impact on increasing their income as well as social welfare.